Antioxidant and antibacterial activity of root and seed extracts of Achyranthes aspera - Meher,; D MANOHAR RAO, (International Journal of Phytomedicine, 2015)
Achyranthes aspera L., a common weed belonging to Amaranthaceae family, possessing many Ayurvedic, Unani-Tibbi, Homeopathic, Siddha, Naturopathic, medicinal propertiesis widely distributed throughout the tropical world. The objective of the present study is to extract and quantify the polyphenols and flavonoids besides evaluating their antioxidant and antimicrobial activity against eight bacterial reference strains;Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), Proteus vulgaris (ATCC 6380), Salmonella typhimurium (ATCC 25241), Salmonella paratyphi (ATCC 9150), Shigella sonnei (ATCC 25931) and Klebsiella pneumonia (ATCC 27736). The polyphenols and flavanoids of the extracts from both the tissues were quantified separately by Folin-Ciocalteu and Colorimetric methods respectively. The total content of antioxidants of these extracts was assessed separately by the method of Phospho-molybdenum assay, while the antioxidant activity of these extracts was evaluated by a) 1,1-Diphenyl-2-picryl- hydrazyl (DPPH) and b) lipid peroxidation methods. Further, the antibacterial activity of these extracts was evaluated separately by using agar well diffusion assay against the above mentioned eight bacterial reference strains. All the extracts showed the presence of phytochemicals; tannins, terpenoids, steroids, flavonoids and carbohydrates. The polyphenol and flavonoid content of the extracts was found to decrease in the order of seed ethanol > root ethanol>seed aqueous>root aqueous whereas the antioxidant capacity of the extracts was found to decrease in the order of seed ethanol > root ethanol>seed aqueous>root aqueous. The seed ethanol and root ethanol high DPPH scavenging activity and lipid peroxidation activity compared to seed and root aqueous. The result of this study proves that extracts are good source of antioxidants and antimicrobial agents to use them as a broad spectrum of investigation in medicines.